Pulmonary Hypertension and COVID-19 - Castiglione, Laura; Droppa, Michal (Hämostaseologie, 2021)
Coronavirus disease 2019 (COVID-19) is a primary respiratory infectious disease, which can result in pulmonary and cardiovascular complications. From its first appearance in the city of Wuhan (China), the infection spread worldwide, leading to its declaration as a pandemic on March 11, 2020. Clinical research on SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) suggests that the virus may determine changes in the pulmonary hemodynamics through mechanisms of endothelial dysfunction, vascular leak, thrombotic microangiopathy, and venous thromboembolism that are similar to those leading to pulmonary hypertension (PH). Current available studies report echocardiographic signs of PH in approximately 12 to 13% of hospitalized patients with COVID-19. Those with chronic pulmonary obstructive disease, congestive heart failure, pulmonary embolism, and prior PH are at increased risk to develop or worsen PH. Evidence of PH seems to be associated with increased disease severity and poor outcome. Because of the importance of the pulmonary hemodynamics in the pathophysiology of COVID-19, there is growing interest in exploring the potential therapeutical benefits of inhaled vasodilators in patients with COVID-19. Treatment with inhaled nitric oxide and prostacyclin has shown encouraging results through improvement of systemic oxygenation, reduction of systolic pulmonary arterial pressure, and prevention of right ventricular failure; however, data from randomized control trials are still required.
Keywords: COVID-19; pulmonary hypertension; right heart failure